PRAGMATISM OF RANDOMIZED CLINICAL TRIALS ON RANIBIZUMAB FOR THE TREATMENT OF DIABETIC MACULAR EDEMA: Impact on Clinical Outcomes. Issue 5 (May 2020) - Stewart, Stephen; Yeong, Jian Lee; Virgili, Gianni; Azuara-Blanco, Augusto; Lois, Noemi
Abstract : Purpose: To evaluate the pragmatism and generalizability of randomized clinical trials (RCTs) on ranibizumab for diabetic macular edema and determine whether clinical outcomes would differ based on whether or not patients fulfill the eligibility criteria of these RCTs. Methods: Pragmatism and generalizability of three RCTs on ranibizumab for diabetic macular edema (DRCRnet Protocols I and T, and RESTORE) were rated using the PRECIS-2 tool. A cohort of consecutive patients with diabetic macular edema was assessed to determine whether clinical outcomes differed based on whether or not patients met the RCT eligibility criteria. Univariable and multivariable regression analyses, adjusted for baseline best-corrected visual acuity, central retinal thickness and number of injections received, were used. Results: All RCTs were rated as being more pragmatic than explanatory, with DRCRnet trials being the most pragmatic. Of the 216 eyes (176 patients) included in the cohort, 63% would have met eligibility criteria for Protocol T, 61% for Protocol I, and 56% for RESTORE. When adjusted for best-corrected visual acuity, central retinal thickness, and number of ranibizumab injections received, there were no statistically significant differences in best-corrected visual acuity or central retinal thickness found between "eligible" and "ineligible" patients. Conclusion: Randomized clinical trials evaluating ranibizumab for diabetic macular edema were more pragmatic than explanatory. "Ineligible" patients still benefited from ranibizumab therapy. Abstract : Randomized clinical trials evaluating ranibizumab for DME were found to be more pragmatic than explanatory. Patients in a "real-life" clinical setting who would be ineligible for landmark trials achieve similar outcomes to eligible patients.